Enumeration of viruses and prokaryotes in deep-sea sediments and cold seeps of the Gulf of Mexico - Kellogg, C A (Deep-Sea Research. Part II: Topical Studies in Oceanography, 2010)
Little is known about the distribution and abundance of viruses in deep-sea cold-seep environments. Like hydrothermal vents, seeps support communities of macrofauna that are sustained by chemosynthetic bacteria. Sediments close to these communities are hypothesized to be more microbiologically active and therefore to host higher numbers of viruses than non-seep areas. Push cores were taken at five types of Gulf of Mexico habitats at water depths below 1000 m using a remotely operated vehicle (ROV). The habitats included non-seep reference sediment, brine seeps, a microbial mat, an urchin field, and a pogonophoran worm community. Samples were processed immediately for enumeration of viruses and prokaryotes without the addition of a preservative. Prokaryote counts were an order of magnitude lower in sediments directly in contact with macrofauna (urchins, pogonophorans) compared to all other samples (107 vs. 108 cells g−1 dry weight) and were highest in areas of elevated salinity (brine seeps). Viral-Like Particle (VLP) counts were lowest in the reference sediments and pogonophoran cores (108 VLP g−1 dry wt), higher in brine seeps (109 VLP g−1 dry wt), and highest in the microbial mats (1010 VLP g−1 dry wt). Virus-prokaryote ratios (VPR) ranged from {<}5 in the reference sediment to {>}30 in the microbial mats and {>}60 in the urchin field. VLP counts and VPR were all significantly greater than those reported from sediments in the deep Mediterranean Sea and in most cases were higher than recent data from a cold-seep site near Japan. The high VPR suggest that greater microbial activity in or near cold-seep environments results in greater viral production and therefore higher numbers of viruses.
Keywords: ROV Jason (Remotely Operated Vehicle)